Genomic analysis for preweaning calf mortality in Nellore cattle - Garzón, Natalia Andrea Marín [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
Preweaning calf mortality is one of main causes of economic losses in beef cattle, since most of economic incomes are represented by the number of weaned calves available for sale. It is also detrimental for genetic progress due to the reduction of young candidates for selection. The inclusion of molecular markers in genetic analysis allows a better understanding of genetic mechanisms underlying calf mortality. The objectives of this study were: i) to estimate direct and maternal heritability of preweaning calf mortality in Nellore cattle and ii) to seek for genomic regions and candidate genes affecting direct and maternal effects of preweaning calf mortality in Nellore cattle. Variance components were estimated via Bayesian Inference using a threshold animal model, that included the systematic effects of contemporary group, birth weight as linear covariate, and age of dam at calving as linear and quadratic covariates. The direct and maternal genetics, and the residual were fitted as random effects. The final dataset used contained phenotypic records on 67,196 animals, offspring of 1,469 sires and 30,970 dams. The SNPs effects were estimated based on the weighted single-step GBLUP approach, using information of 8,443 genotyped animals with 410,936 SNPs. Direct and maternal heritability estimates were of 0.2143±0.0348 and 0.0137±0.0066, respectively. The top 10 genomic regions accounted for 13.61 and 14.23% of direct and maternal additive genetic variance and harbored a total of 63 and 48 positional candidate genes, respectively. Two overlapping regions located on BTA2 were identified, harboring common candidate genes for direct and maternal effects. The candidate genes RUNX3, CLIC4 and RCAN3, present into these regions, are involved in apoptotic pathway, signaling transducing, response to stimulus and immunological system. The genes CD53, LAMTOR5, ARF6, STPG1, CTNNA2, RALYL, CDKL1, and PROK1, were identified as candidates for direct effects of preweaning mortality as they are involved in cell regulation, preservation and survival. The genes CRADD and MAP3K5 were associated with maternal effects. These genes are involved in apoptosis, an important pathway for the normal development of pregnancy. These physiological roles may control genetic mechanism underlying preweaning calf mortality.

A mortalidade pré-desmame de bezerros é uma das principais causas de perdas econômicas em bovinos de corte, uma vez que a maior parte da renda econômica é representada pelo número de bezerros desmamados disponíveis para venda. Esta também é prejudicial para o progresso genético devido à redução de candidatos jovens para a seleção. A inclusão de marcadores moleculares na análise genética permite uma melhor compreensão dos mecanismos genéticos subjacentes à mortalidade de bezerros. Os objetivos deste estudo foram: i) estimar a herdabilidade direta e materna da mortalidade pré-desmame em bovinos Nelore e ii) buscar regiões genômicas e genes candidatos afetando os efeitos diretos e maternos da mortalidade pré-desmame em bovinos Nelore. Os componentes de variância foram estimados por Inferência Bayesiana usando um modelo animal de limiar, que incluiu os efeitos sistemáticos do grupo contemporâneo, peso ao nascer como covariável linear e a idade da mãe ao parto como covariável linear e quadrática. Os efeitos genéticos diretos e maternos, e o resíduo foram ajustados como efeitos aleatórios. O conjunto final de dados utilizado continha registros fenotípicos em 67.196 animais, descendentes de 1.469 touros e 30.970 vacas. Os efeitos dos SNPs foram estimados com base na abordagem weighted single step GBLUP, usando informações de 8.443 animais genotipados com 410.936 SNPs. As estimativas de herdabilidade direta e materna foram de 0,2143±0,0348 e 0,0137±0,0066, respectivamente. As dez principais regiões genômicas explicaram 13,61 e 14,23% da variação genética aditiva direta e materna e abrigaram um total de 63 e 48 genes candidatos posicionais, respectivamente. Duas regiões sobrepostas localizadas no BTA2 foram identificadas, abrigando genes candidatos comuns para efeitos diretos e maternos. Os genes candidatos RUNX3, CLIC4 e RCAN3, presentes nessas regiões, estão envolvidos na via apoptótica, transdução de sinalização, resposta a estímulos e sistema imunológico. Os genes CD53, LAMTOR5, ARF6, STPG1, CTNNA2, RALYL, CDKL1 e PROK1, foram identificados como candidatos para o efeito direto da mortalidade pré-desmame, uma vez estão envolvidos na regulação, preservação e sobrevivência celular. Os genes CRADD e MAP3K5 foram associados ao efeito materno. Esses genes estão envolvidos em apoptose celular, uma rota importante para o desenvolvimento normal da gravidez. Esses papéis fisiológicos podem controlar os mecanismos genéticos subjacente à mortalidade pré-desmame de bezerros
Análise genômica para mortalidade pré-desmame em bovinos da raça Nelore
Keywords: Beef cattle; Gene; Heritability; Single step GWAS; Survival; Bovinos de corte; Herdabilidade; Sobrevivência